Emotional Consequences and Coping Techniques of Higher Education Dyslexic Learners in Pakistan: Multiple Case Analysis (Journal of Social Sciences Review, 2023)
The main purpose of the current study was to explore higher education dyslexic learners' (HEDLs) awareness, experiences, emotional consequences, and coping strategies for dyslexia.  It was a qualitative study with a case study method. Eight dyslexic students (Male=4, Female=4) were selected through the snowball sampling (purposive sampling) technique. The participants were from higher education institutions in Punjab. A semi-structured interview guide was developed through literature and expert opinion for the collection of data. The participants were interviewed face-to-face. All the interviews were transcribed. For the data analysis, a multiple-case analysis model explaining similar and alternating themes was used. According to the findings, the participants were aware of dyslexia. They faced academic challenges, as well as family relationship problems. They had a negative effect of emotional consequences which affected their academic and personal lives. All the participants used positive and negative coping strategies to deal with their learning disabilities. Teachers should be trained and educated about teaching dyslexia students like normal students.
Keywords: Dyslexia; Emotional Consequences; Dyslexic Learners; Learning Disability